Ursolic Acid Regulates Cell Cycle and Proliferation in Colon Adenocarcinoma by Suppressing Cyclin B1 - Minhui Yang; Changxiao Hu; Yibo Cao; Yibo Cao; Wanling Liang; Xiangdong Yang; Tianbao Xiao (Frontiers Media S.A., 2021)
Aims: The biological functions of cyclin B1 (CCNB1) in colon adenocarcinoma (COAD) will be explored in this study. Furthermore, the therapeutic effects and potential molecular mechanisms of ursolic acid (UA) in COAD cells will also be investigated in vitro.Methods: COAD data were obtained from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. Differentially expressed genes (DEGs) were determined with differential analysis. The biological functions of CCNB1 were analyzed through the GeneCards, the Search Tool for the Retrieval of Interacting Genes (STRING), and the Database for Annotation, Visualization, and Integrated Discovery (DAVID) databases. Therapeutic effects of UA on COAD cell lines HCT-116 and SW-480 were analyzed by CCK-8 and high-content screening (HCS) imaging assay. Flow cytometry was utilized to detect cell cycle changes of SW-480 and HCT-116 cells. Levels of mRNA and expression proteins of HCT-116, SW-480, and normal colon epithelial cells NCM-460 were determined by qRT-PCR and western blot.Results: CCNB1 was highly expressed and acted as an oncogene in COAD patients. CCNB1 and its interacting genes were significantly enriched in the cell cycle pathway. UA effectively inhibited the proliferation and injured COAD cells. In addition, UA arrested cell cycle of COAD cells in S phase. With regard to the molecular mechanisms of UA, we demonstrated that UA can significantly downregulate CCNB1 and its interacting genes and proteins, including CDK1, CDC20, CCND1, and CCNA2, which contributed to cell cycle blocking and COAD treatment.Conclusion: Results from this study revealed that UA possesses therapeutic effects on COAD. The anti-COAD activities of UA are tightly related to suppression of CCNB1 and its interacting targets, which is crucial in abnormal cell cycle process.